Designing of Enterprise Architecture for Vocational High School Information System Using TOGAF Architecture Development Method - S Siswanto; I D Sumitra (Peneliti.net, 2020)
The purpose of this research is to design a blueprint that can be used to meet the needs of business functions the Vocational High School of XYZ. In this research, the method used to design Enterprise Architecture was The Open Group Architecture Framework Architecture Development Method (TOGAF ADM). The phases of TOGAF ADM applied in this design are the Preliminary Phase, Architecture Vision Phase, Business Architecture Phase, Information System Architecture Phase, and Technology Phase. The results of this research in the form of preliminary phase up to the technology phase from the TOGAF ADM that can be used for information system development in the Vocational High School of XYZ so that the next research is expected can meet all the TOGAF ADM phases.